Injuries in female collegiate swimmers due to swimming and cross training - McFarland, E. G.; Wasik, M. (Clinical Journal of Sport Medicine, 1996)
OBJECTIVE: To identify and compare the nature and frequency of training and cross-training injuries incurred by members of a women's collegiate swim team. DESIGN: A longitudinal survey of training-room and medical records for 7 years, classifying injuries by diagnosis and time lost from participation. SETTING: Division I women's collegiate swimming program, United States. PARTICIPANTS: All swimmers in a Division I women's collegiate swimming program over 7 years, for a total of 68 swimmers. ASSESSMENT OF RISK FACTOR: Not applicable. INTERVENTION: Not applicable. MAIN OUTCOME MEASURES: "Injury" was defined as any contact with a trainer or physician that resulted in evaluation or treatment. Each injury was categorized with respect to (a) activity during which injury was incurred; (b) diagnosis, including body part injured; (c) time lost from participation in practice or competition; and (d) severity, i.e., minor (< or = 7 days), moderate (7-21 days), and major (> 21 days). An "Exposure" was defined as participation in one practice session or competition. MAIN RESULTS: The overall injury rate per 1,000 exposures per athlete was 2.12; 44% of injuries were due to swimming, 44% to cross training, and 11% to activities unrelated to athletics. Cross-training injuries occurred primarily in the lower extremities, while swimming injuries occurred more commonly in the upper extremities. The ratio of upper to lower extremity injuries due to swimming was 3:1, whereas the ratio for cross training was 1:4. CONCLUSIONS: Injuries to swimmers occur at a lower rate per exposure than to other collegiate athletic populations. Swimming injuries occurred primarily in the upper extremities, especially the shoulder. Lower extremity injuries occurred primarily due to cross training. We conclude that swimming is relatively safe compared to other collegiate sports, but special care should be used in designing injury-avoiding cross-training programs.